Meningkatkan Kesiapan Sekolah dalam Edukasi Kesehatan Reproduksi bagi Siswi Tunagrahita: Studi Pengabdian di SLB Jakarta Pusat - Anggraini, Dewi; Sari, Irma Permata; Nursanti, Irna (Pakis Journal Institute, 2025)
Reproductive health education for intellectually disabled female students in special schools remains inadequate due to the lack of tailored teaching modules, teacher training, and curriculum support. This community service program, initiated by nurses from the Department of Maternity and Reproductive Health Nursing at UMJ, aimed to enhance school readiness through three main interventions: provision of menstrual kits, installation of educational posters, and teacher training for 10 special school teachers. The program also targeted 15 intellectually disabled students and representatives of parents and school principals as policymakers. Nurses played a key role in designing instructional media, facilitating interactive workshops, and guiding pre‑post test evaluations. Implemented at SLB B‑C Cempaka Putih Central Jakarta from October 2024 to June 2025, this participatory approach yielded a 35% average increase in teacher knowledge scores, 85% respondent satisfaction, and positive student behavioral changes in recognizing menstrual signs and maintaining hygiene. This success demonstrates the enhanced capacity of nurses and schools to create an inclusive, supportive, and responsive environment for the reproductive needs of intellectually disabled adolescents.